2022
DOI: 10.1038/s41586-022-04696-z
|View full text |Cite|
|
Sign up to set email alerts
|

Fundamental immune–oncogenicity trade-offs define driver mutation fitness

Abstract: Missense driver mutations in cancer are concentrated in a few hotspots1. Various mechanisms have been proposed to explain this skew, including biased mutational processes2, phenotypic differences3–6 and immunoediting of neoantigens7,8; however, to our knowledge, no existing model weighs the relative contribution of these features to tumour evolution. We propose a unified theoretical ‘free fitness’ framework that parsimoniously integrates multimodal genomic, epigenetic, transcriptomic and proteomic data into a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 38 publications
2
17
0
Order By: Relevance
“…Interestingly, a recent model explains the presence of hotspots events in driver genes in terms of a trade-off fitness advantage of oncogenicity versus immunogenicity, possibly confirming the differences we observe in the distribution of mutations between the escaped and non-escaped cohorts [15]. As we could expect from our findings with the distribution of mutations, the proportion of mutational signatures also varies between escape+ and escape-.…”
Section: Discussionsupporting
confidence: 89%
“…Interestingly, a recent model explains the presence of hotspots events in driver genes in terms of a trade-off fitness advantage of oncogenicity versus immunogenicity, possibly confirming the differences we observe in the distribution of mutations between the escaped and non-escaped cohorts [15]. As we could expect from our findings with the distribution of mutations, the proportion of mutational signatures also varies between escape+ and escape-.…”
Section: Discussionsupporting
confidence: 89%
“…Neoantigen-based vaccines showed limited clinical response in previous trials (5,53). This might have been due to poor candidate selection or because of a dysregulated T cell state in the treated patients.…”
Section: Discussionmentioning
confidence: 99%
“…It has long been postulated that the immune system shapes tumors by eliminating clones expressing immunogenic antigens in a process called immunoediting ( 39 41 ). We have also recently shown that there is a trade-off between tumorigenicity of a mutation and its immunogenicity ( 42 ). Clones that evade elimination would either enter a state of equilibrium with the immune system or manage to evade it completely, such that it manifests clinically.…”
Section: Discussionmentioning
confidence: 99%